Analysis of Exocyst Subunit EXO70 Family Reveals Distinct Membrane Polar Domains in Tobacco Pollen Tubes - Sekereš, Juraj; Pejchar, Přemysl; Šantrůček, Jiří; Vukašinović, Nemanja; Žárský, Viktor; Potocký, Martin (Plant physiology, 2017)
The vesicle-tethering complex exocyst is one of the crucial cell polarity regulators. The EXO70 subunit is required for the targeting of the complex and is represented by many isoforms in angiosperm plant cells. This diversity could be partly responsible for the establishment and maintenance of membrane domains with different composition. To address this hypothesis, we employed the growing pollen tube, a well-established cell polarity model system, and performed large-scale expression, localization, and functional analysis of tobacco (Nicotiana tabacum) EXO70 isoforms. Various isoforms localized to different regions of the pollen tube plasma membrane, apical vesicle-rich inverted cone region, nucleus, and cytoplasm. The overexpression of major pollen-expressed EXO70 isoforms resulted in growth arrest and characteristic phenotypic deviations of tip swelling and apical invaginations. NtEXO70A1a and NtEXO70B1 occupied two distinct and mutually exclusive plasma membrane domains. Both isoforms partly colocalized with the exocyst subunit NtSEC3a at the plasma membrane, possibly forming different exocyst complex subpopulations. NtEXO70A1a localized to the small area previously characterized as the site of exocytosis in the tobacco pollen tube, while NtEXO70B1 surprisingly colocalized with the zone of clathrin-mediated endocytosis. Both NtEXO70A1a and NtEXO70B1 colocalized to different degrees with markers for the anionic signaling phospholipids phosphatidylinositol 4,5-bisphosphate and phosphatidic acid. In contrast, members of the EXO70 C class, which are specifically expressed in tip-growing cells, exhibited exocytosis-related functional effects in pollen tubes despite the absence of apparent plasma membrane localization. Taken together, our data support the existence of multiple membrane-trafficking domains regulated by different EXO70-containing exocyst complexes within a single cell.
Keywords: Protein Isoforms; Exocytosis; elektroforéza v polyakrylamidovém gelu; sekvence aminokyselin; Gene Expression Regulation, Plant; proteomika; vývojová regulace genové exprese; Cell Membrane; Microscopy, Confocal; Chromatography, High Pressure Liquid; vysokoúčinná kapalinová chromatografie; konfokální mikroskopie; rostlinné proteiny; polymerázová řetězová reakce s reverzní transkripcí; Gene Expression Regulation, Developmental; Base Sequence; sekvence nukleotidů; exocytóza; Electrophoresis, Polyacrylamide Gel; Proteomics; tabák; protein - isoformy; Amino Acid Sequence; fylogeneze; Plant Proteins; Pollen Tube; regulace genové exprese u rostlin; buněčná membrána; Reverse Transcriptase Polymerase Chain Reaction; hmotnostní spektrometrie s elektrosprejovou ionizací; pylová láčka; sekvenční homologie aminokyselin; Nicotiana; Phylogeny; Spectrometry, Mass, Electrospray Ionization; Sequence Homology, Amino Acid